A COMPARATIVE STUDY OF EIF2А KINASES IN PLANT AND MAMMALIAN ANTIVIRAL RESPONSES - Synytsia, Mariia (Collection of scientific papers «ΛΌГOΣ», 2025)
Absolutely all living organisms suffer from viruses. This applies to plants as well as to animals. Despite the evolutionary distance between them, each kingdom deploys rapid innate defense mechanisms, relying on translational control and regulating protein synthesis as a key defensive mechanism.